Exploring The Intersection of Vocational Student Resilience in The Workplace and Religious Beliefs: A Literature Review - Nurjanah, Fitri; Prihantono, Muhamad Rifqi; Ramadhan, Idang; Arifudin, Moch. (Proceeding International Conference on Religion, Science and Education, 2025)
Vocational graduates have significant unemployment rates, with just 45% of them working in sectors linked to their degrees, demonstrating a mismatch between education and job market demands. The VUCA age, defined by volatility, uncertainty, complexity, and ambiguity, has necessitated the development of resilience skills among vocational students in the face of disruptions in the workplace. Resilience is the ability to recover or cope with adverse situations. Spiritual and religious beliefs may be associated with important “resilience resources”. This area of study offers valuable insights, and how they might help educators and policymakers in developing more effective support systems that use religious beliefs as resilience resources to improve the performance of students. The paper adopts a literature review method to answer the question “how the intersection between vocational student resilience in the workplace and religious beliefs?”. Exploring the link between religious beliefs and resilience of vocational students in the workplace is a multifaceted issue that cover factors such as work attitudes, work readiness, stress management, and job satisfaction. According to this study, religious beliefs have an indirect impact on how vocational learners may be resilient in working environments. Religious beliefs have been noted to have an impact on job readiness, job satisfaction, work attitudes, and stress management of students while doing internships in the workplace, all of which contribute to an increase in the students resilience in overcoming challenges, ability to adapt to adversity, and achieving success.